2018
DOI: 10.15416/pcpr.v3i2.20005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endophytic Bacterial Isolated from Oil Palm Plants with Anti-Fungal Acitvity against Ganoderma boninense

Abstract: Endophytic bacteria is an excellent candidates for the biological control of pathogenic fungi in plantations. The objectives of this study were to isolate and examine anti-fungal activity of endophytic bacteria from oil palm plantations in South Kalimantan against Ganoderma boninense. This research was performed in three phases, i.e., isolation, selection, and assessment of endophytic bacteria isolates against Ganoderma boninense. A total of 126 colonies of endophytic bacteria were isolated. The result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…An endophytic bacteria isolate, identified as Bacillus cereus , demonstrated strong antifungal activity against G. boninense . This suggests the potential of oil palm plantation endophytic bacteria as a natural control method for Ganoderma infection [ 336 ]. Malaysian seaweed extracts inhibit G. boninense , offering potential antifungal compounds against basal stem rot in oil palm [ 337 ].…”
Section: Research On Disease Management Strategies To Control Basal S...mentioning
confidence: 99%
“…An endophytic bacteria isolate, identified as Bacillus cereus , demonstrated strong antifungal activity against G. boninense . This suggests the potential of oil palm plantation endophytic bacteria as a natural control method for Ganoderma infection [ 336 ]. Malaysian seaweed extracts inhibit G. boninense , offering potential antifungal compounds against basal stem rot in oil palm [ 337 ].…”
Section: Research On Disease Management Strategies To Control Basal S...mentioning
confidence: 99%
“…Pengujian anti-jamur bakteri tersebut terhadap jamur patogen Colletothricum capsici memiliki daya hambat 28,48%, pengujian terhadap jamur C. gloeosporioides memiliki daya hambat 19,99% dan pengujian terhadap Fusarium oxysporum sub sp cubense memiliki daya hambat 14,54% (Resti et al, 2017). Hasil pengujian ini juga lebih baik daripada pengujian Mardiah (2018), B.cereus memiliki kemampuan anti-jamur dan menekan pertumbuhan Ganoderma boninense dengan daya hambat 62,22%. Sedangkan Bacillus oryzicola YC7007 yang diisolasi dari perakaran tanaman padi mampu menekan partumbuhan berbagai jenis jamur patogen tanaman padi, menginduksi ketahanan dan meningkat-kan pertumbuhan tanaman padi (Chung et al, 2015).…”
Section: Hasil Uji Antagonis Bakteri Endofit Terhadap C Oryzaeunclassified
“…Therefore, endophytic bacteria are relatively novel in biocontrol disease of research. [11] in her research was successfully identified endophytic bacteria of Bacillus cereus which has antagonistic properties against Ganoderma boninense in oil palm plants. The studies of bioactive compounds which involves in antagonistic process have not been carried out yet.…”
Section: Introductionmentioning
confidence: 99%